Effects of Guided Antenatal Education Support Programs on Postnatal Depression, Social Support, and Life Satisfaction among First-time Mothers in Kelantan, Malaysia - Badrin, Salwismawati; Badrin, Salziyan; Raja Gopal, Raja Lexshimi; Johan Noor, Shah Reza (Nurse Media Journal of Nursing, 2021)
Background: First-time mothers may experience postnatal depression and a lack of social support, affecting their life satisfaction. However, there is a lack of studies investigating the application of guided antenatal education support programs to deal with such issues.Purpose: The study aimed to evaluate the effects of guided antenatal education support programs on postnatal depression, social support, and life satisfaction among first-time mothers.Methods: This quasi-experimental study involved a total of 72 first-time mothers. Convenience sampling was applied for participant selection, and no randomization was used. The participants were equally divided into the intervention group and the control group. A self-administrated questionnaire was used for data collection during the antenatal period (pretest) and six weeks postpartum (posttest). The risk of postnatal depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS). In addition, the Multidimensional Scale of Perceived Social Support (MSPSS) and the Satisfaction with Life Scale (SWLS) were used to assess social support, and life satisfaction, respectively. The intervention group received a guided antenatal education support program, consisting of antenatal education sessions plus an extra 15-minute discussion and a support guidebook. The data were analyzed using a paired t-test and an independent t-test.Results: There was a significant reduction in the risk of postnatal depression score in the intervention group (p<0.05) after receiving the guided antenatal education compared to the control group. Also, there was a significant increment of life satisfaction score (p<0.05) and social support score (p<0.05) after receiving guided antenatal education in the intervention group.Conclusion: The guided antenatal education support is beneficial to reduce postnatal depression and increase life satisfaction and social support. Nurses and midwives should provide an integration of psychoeducation for first-time mothers, especially during pregnancy.